JEAN PIAGET THEORY PERSPERCTIVE ON INTERPERSONAL COMMUNICATION BETWEEN PARENTS AND CHILDREN IN THE STAGE OF GADGET ADDICTION - Olly Aurora; Fadla Fauzan Syanu; Yanti Trianita; Iqbal Al Khazim (Universitas Gunadarma, 2023)
The purpose of this study is to analyze how interpersonal communication occurs between parents and children in the stage of gadget addiction using the perspective of Jean Piaget's theory. Researchers used the phenomenological paradigm to explore informants' experiences about the interpersonal communication process that occurred. In-depth interviews were conducted with informants to explore communication patterns between parents and their children. The results showed that the forms of communication carried out by parents to children in gadget addiction were divided into 3 groups, namely in a liberating, democratic, and authoritarian manner. The most intense communication process occurs in groups that use democracy. Using Piaget's perspective, the process of children's addiction begins at the Preoperational stage, where children begin to represent the world with symbols, words, language, and images.